Applications of textile based electrodes in gait analysis: Prolimb Project - Catarino, André P. (2013)
This paper presents the application of textile based electrodes for surface electromyography embedded in a wearable locomotion data capture system for gait analysis. The system that is under development will allow the measurement of several locomotion-related parameters in a practical and non-invasive way, comfortable to the user, reusable which can be used by patients from light to severe impairments or disabilities. The present paper gives an overview of the research, regarding the design of the textile electrodes, the textile support, and communications.